PEMBEBASAN LAHAN TOL AKSES PELABUHAN PATIMBAN KABUPATEN SUBANG - Haryono, Rakhmat; Daris, Ahmad (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
The Patimban Port development plan requires optimal accessibility through the construction of a toll road connecting the port with the Cipali Toll Road. The project requires land acquisition of 338.6 hectares with 1,395 parcels of land spread across several sub-districts. This study identifies land requirements, estimated physical and non-physical compensation costs, and land certification costs with a total estimated cost of IDR 1.62 trillion. The data used includes primary sources from stakeholders and secondary data from relevant regulations and planning documents.